Comprehensive parametric analysis, sizing, and performance evaluation of a tubular direct contact membrane desalination system driven by heat pipe-based solar collectors. (15th December 2022) - El-Agouz, S.A.; Abd Elbar, Ayman Refat; Aboghazala, Ali M.; Shahin, Mohammad; Zakaria, M.Y.; Esmaeil, Khaled Khodary; Zayed, Mohamed E.
Highlights: A detailed model was developed to simulate a DCMD system powered by solar heat pipe collectors. Parametric analysis was conducted to figure out the influence of design parameters on system performance. No. of the utilized solar collectors, feed flow rate, and cooling water flow rate were the most sensitive parameters. Daily freshwater yield of 36 L achieved with a 1.0 m 2 tubular module and 9.0 m 2 solar field. Abstract: Feed seawater heating is one of the crucial bottlenecks in membrane desalination (MD) systems. The interest of usage solar energy techniques for feed seawater preheating in MD systems is recently regarded as an improvement path for sustainable distillate production. This study presents a conceptual design, theoretical modeling, and comprehensive parametric analysis of a tubular direct contact membrane desalination system (TDCMDS) driven by heat pipe-based solar collectors (HPSCs). An improved theoretical model performed in MATLAB software was conducted to simulate the hybrid solar TDCMDS operation in order to analyse its performance in the climate conditions of Tanta, Egypt. The effects of the number of utilized solar collectors, feed seawater flowrate, cooling water flowrate, and utilization of additional electric heaters on the energy performance of the solar TDCMDS are parametrically investigated. The findings show that the number of the utilized solar collectors, feed seawater flowrate, and cooling water flowrate, were the most sensitive to the performance of the solar TDCMDS, which should be desired to be 5.0 ≥ n ≥ 2.0, 20.0 lpm, and 5.0 lpm, respectively, in the design of the TDCMDS to maximize the freshwater production. Moreover, the maximum permeates flux are 0.45, 0.39, 0.32, and 0.25 kg/h per m 2 of solar collecting area with total daily freshwater production of 35.0, 24.60, 15.48, and 7.95 kg/day by integrating five, four, three, and two HPSCs connected in series, respectively, compared to only 0.08 kg/h.m 2 and 1.44 kg/day when coupling one solar collector at feed seawater and cooling water flowrates of 20 and 5.0 lpm, respectively. Conclusively, it can be recommended that this investigation provides an emerging strategy for designing solar-based MD systems.